Chronic and terminal illness - Payne, Sheila (Oxford University Press, 2001)
Most chronically and terminally ill patients are cared for in their own homes and represent a major yet free resource. These patients are not in hospitals or hospices and their day-to-day care is provided by family and friends at home. Carers are an invaluable resource and there is an increasing amount of research into their role and the experiences in caring for the terminally ill, patients with cancer and patients with other chronic diseases